2021
DOI: 10.1192/j.eurpsy.2021.29
|View full text |Cite
|
Sign up to set email alerts
|

The use of personal protective equipment as an independent factor for developing depressive and post-traumatic stress symptoms in the postpartum period

Abstract: Background: New recommendations regarding the use of personal protective equipment (PPE) during delivery have changed the maternal birth experience. In this study, we investigated the mental perceived impact of PPE use during delivery on the development of maternal postpartum depression (PPD) and post-traumatic stress symptoms (PTSS).Methods: This was a multicenter, retrospective cohort study concerning women who delivered during the COVID-19 pandemic first lockdown period in Israel. Postpartum women were appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…] 2021 US 2402 N/A 100 Zhou Y [ 107. ] 2021 China 1266 N/A 101 Gluska H [ 108. ] 2021 Israel 421 N/A 102 Liu CH [ 109.…”
Section: Resultsmentioning
confidence: 99%
“…] 2021 US 2402 N/A 100 Zhou Y [ 107. ] 2021 China 1266 N/A 101 Gluska H [ 108. ] 2021 Israel 421 N/A 102 Liu CH [ 109.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggest that 14.8% to 40.7% (median = 35%) of mothers with PPD still met criteria for major depression with EPDS > 13 at less than 3 month (n = 8 studies 12,16,18,20,21,23,28,38 ); 27.4% at 1 week (n = 1 study 30 ) 38% to 44% (median = 39%) at 1 month (n = 3 studies 6,40,41 ); 30% to 39% (median = 36%) at 4 to 12 weeks (n = 3 studies 15,24,47 ); 12% to 36.3% (median 23.3%) at 2 months (n = 4 studies 4,27,32,44 ); and 30% to 80% (median = 33%) at 3 months (n = 6 studies 4,14,22,26,42,46 ); 9.6% to 60% (median = 27%), duration of months is not applicable (n = 11 studies 13,17,19,25,29,34,39,43,45,46 ), 12.4% at <5 months (n = 1 study 22 ). Overall, these findings suggest that at any time point between 1 week and <5 months postpartum, about 27% of mothers diagnosed with PPD still meet criteria for depression.…”
Section: Prevalence Of Ppd Periodmentioning
confidence: 99%
“…Hadar et al [31] investigated women during the first blockade of the COVID-19 epidemic and showed that those with higher scores had higher scores of EPDS and a higher risk of PPD compared to those with lower protective equipment impact scores home, and the reason for the impact [32] may be that the use of personal protective equipment may be an obstacle to communication between doctors and patients, and the psychological support patients receive would be correspondingly reduced.…”
Section: The Use Of Personal Protective Equipmentmentioning
confidence: 99%